Arterial wall stress controls NFAT5 activity in vascular smooth muscle cells - Scherer, Clemens Martin; Pfisterer, Larissa; Wagner, Andreas H.; Zappe, Maren; Cattaruzza, Marco; Hecker, Markus; Korff, Thomas (Journal of the American Heart Association, 2014)
Nuclear factor of activated T‐cells 5 (NFAT5) has recently been described to control the phenotype of vascular smooth muscle cells (VSMCs). Although an increase in wall stress or stretch (eg, elicited by hypertension) is a prototypic determinant of VSMC activation, the impact of this biomechanical force on the activity of NFAT5 is unknown. This study intended to reveal the function of NFAT5 and to explore potential signal transduction pathways leading to its activation in stretch‐stimulated VSMCs.